The presentation of the 'divided self' in John Banville's novels - Stoyanova, Antonia (2023)
This thesis focuses on the writing style of John Banville and, more particularly, on one of the major narrative features in his works, that of the ‘divided self’. As one of the recognised masters of style of our time, John Banville has honed his own unique style of writing. The typical Banville novel is a first-person retrospective narrative of an aging male character troubled by his painful memories of failure and loss. In a struggle to cope with their traumatic life experiences, Banville’s protagonists attempt to find answers to haunting existential questions and rediscover their identities in the face of emotional fragmentation. This sense of dislocation and displacement thus emerges as a major theme of Banville’s fiction and his works generally revolve around the internal conflicts of a ‘divided self’.